2003
DOI: 10.1016/s0741-5214(03)00336-7
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative risk factors for carotid endarterectomy: defining the patient at high risk

Abstract: CEA can be safely performed in patients deemed at high risk, including those aged 80 years or older and others with significant comorbid conditions, with combined stroke and mortality rates comparable to those found in randomized trials, ie, the Asymptomatic Carotid Atherosclerosis Study and the North American Symptomatic Carotid Endarterectomy Trial. Contralateral occlusion may be a predictor for moderately increased perioperative risk and for reduced long-term survival. Caution may be warranted in asymptomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
86
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(96 citation statements)
references
References 20 publications
7
86
0
3
Order By: Relevance
“…22 Other authors published studies about the definition and conduct in high-risk patients. [60][61][62] Gasparis et al 60 defined high risk in two groups: physiological risk and anatomic risk. In the former, they included 80 patients older than 80 years, 11 with AMI over the past 6 months, 16 with heart failure, chronic pulmonary occlusive disease and 13 with serum creatinine levels above 3 mg/dL.…”
Section: High-risk Patients For Carotid Endarterectomymentioning
confidence: 99%
“…22 Other authors published studies about the definition and conduct in high-risk patients. [60][61][62] Gasparis et al 60 defined high risk in two groups: physiological risk and anatomic risk. In the former, they included 80 patients older than 80 years, 11 with AMI over the past 6 months, 16 with heart failure, chronic pulmonary occlusive disease and 13 with serum creatinine levels above 3 mg/dL.…”
Section: High-risk Patients For Carotid Endarterectomymentioning
confidence: 99%
“…Because age greater than 80 years is considered as one of the risk factors identified by the SAPPHIRE trial (Table 1), the view of old age as a risk factor appears to have been widely adopted. However, many of the studies that indicated age as a risk factor did not detect a strong, but only a "slight", correlation with risk [6][7][8]. Although age can be a risk factor for CEA at present, it does not appear to be a factor precluding the use of CEA for carotid artery stenosis in the elderly.…”
Section: Discussionmentioning
confidence: 94%
“…However, the conclusions of these studies and reviews vary. Several studies reported that age is a risk factor for surgery, while others indicated the contrary [6][7][8][9]. Because age greater than 80 years is considered as one of the risk factors identified by the SAPPHIRE trial (Table 1), the view of old age as a risk factor appears to have been widely adopted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations